Preparation of Photo-Bioelectrochemical Cells With the RC-LH Complex From Roseiflexus castenholzii - Du, Jinsong; Xin, Jiyu; Liu, Menghua; Zhang, Xin; He, Huimin; Wu, Jingyi; Xu, Xiaoling (Frontiers in Microbiology, 2022)
Roseiflexus castenholzii is an ancient green non-sulfur bacteria that absorbs the solar energy through bacteriochlorophylls (BChls) bound in the only light harvesting (LH) complex, and transfers to the reaction center (RC), wherein primary charge separation occurs and transforms the energy into electrochemical potentials. In contrast to purple bacteria, R. castenholzii RC-LH (rcRC-LH) does not contain an H subunit. Instead, a tightly bound tetraheme cytochrome c subunit is exposed on the P-side of the RC, which contains three BChls, three bacteriopheophytins (BPheos), two menaquinones, and one iron for electron transfer. These novel structural features of the rcRC-LH are advantageous for enhancing the electron transfer efficiency and subsequent photo-oxidation of the c-type hemes. However, the photochemical properties of rcRC-LH and its applications in developing the photo-bioelectrochemical cells (PBECs) have not been characterized. Here, we prepared a PBEC using overlapped fluorine-doped tin oxide (FTO) glass and Pt-coated glass as electrodes, and rcRC-LH mixed with varying mediators as the electrolyte. Absence of the H subunit allows rcRC-LH to be selectively adhered onto the hydrophilic surface of the front electrode with its Q-side. Upon illumination, the photogenerated electrons directly enter the front electrode and transfer to the counter electrode, wherein the accepted electrons pass through the exposed c-type hemes to reduce the excited P+, generating a steady-state current of up to 320 nA/cm2 when using PMS as mediator. This study demonstrated the novel photoelectric properties of rcRC-LH and its advantages in preparing effective PBECs, showcasing a potential of this complex in developing new type PBECs.